2019
DOI: 10.33584/jnzg.2019.81.392
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sheep liveweight production and dry matter yield for lucerne-based pastures in spring

Abstract: A five-year dryland grazing experiment explored the relationship between sheep liveweight (LWt) production and dry matter (DM) yield of lucerne-based pastures in spring. In 2011, a randomised complete block experiment with a lucerne monoculture, a lucerne/brome mix and a lucerne/cocksfoot mix were established at Ashley Dene, Canterbury and replicated six times. Pastures were managed under dryland conditions. Ewes with twin lambs at foot grazed in spring and LWt production, DM yield and botanical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Defoliation frequency during a period of soil-water scarcity has previously been shown to have a significant effect in terms of plant fitness to survive and recovery [6]. Results of the WSC reserve status supported the optimal LS range (3)(4) suggested by Ordoñez et al [8] and provided further evidence for managing defoliation frequency in accordance with LS criteria. In a study of defoliation frequency effects based on LS for different grass species, Turner et al [19] showed the importance of species-specific defoliation intervals.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Defoliation frequency during a period of soil-water scarcity has previously been shown to have a significant effect in terms of plant fitness to survive and recovery [6]. Results of the WSC reserve status supported the optimal LS range (3)(4) suggested by Ordoñez et al [8] and provided further evidence for managing defoliation frequency in accordance with LS criteria. In a study of defoliation frequency effects based on LS for different grass species, Turner et al [19] showed the importance of species-specific defoliation intervals.…”
Section: Discussionsupporting
confidence: 64%
“…In a study of defoliation frequency effects based on LS for different grass species, Turner et al [19] showed the importance of species-specific defoliation intervals. Poor productivity and persistence of Bv in field experiments in New Zealand [2,3] could be a consequence of defoliation management based on other species, e.g., perennial ryegrass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation